Update on Neuromyelitis Optica Spectrum Disorder - Holroyd, Kathryn (Curr Opin Ophthalmol, 2020)
PURPOSE OF REVIEW. Neuromyelitis optica spectrum disorder is an autoimmune disease that caused optic neuritis and transverse myelitis. Attacks can cause severe neurological damage leading the blindness and paralysis. Understanding of the immunopathogenesis of this disease has led to major breakthroughs in diagnosis and treatment. In the past 18 months, three successful phase 3 clinical trials have been published using targeted approaches to preventing relapses. RECENT FINDINGS. Updates in epidemiology, imaging, quality of life and treatment for acute relapse and prevention have been published in the past 18 months. Epidemiology studies are distinguishing patients based on their antigen specificity for aquaporin-4 (AQP4) and myelin oligodendrocyte glycoprotein (MOG), which are increasingly recognized as separate immunological conditions. Imaging by MRI and optical coherence tomography continue to be developed as tools to distinguish NMOSD from other diseases. This is especially relevant as the recent clinical trials showed differences in response between AQP4 seropositive and seronegative patients. The three drugs that were tested for prevention of NMOSD relapses were eculizumab, inebilizumab and satralizumab. All of the trials were worldwide, placebo-controlled, double-masked studies that demonstrated a clear benefit with each approach. SUMMARY. Recent research in NMOSD has resulted in improved diagnosis and approved treatments.